GMP synthase is essential for viability and infectivity of Trypanosoma brucei despite a redundant purine salvage pathway. Issue 5 (4th July 2015) - Li, Qiong; Leija, Christopher; Rijo‐Ferreira, Filipa; Chen, Jun; Cestari, Igor; Stuart, Kenneth; Tu, Benjamin P.; Phillips, Margaret A.
Summary The causative agent of human African trypanosomiasis, Trypanosoma brucei, lacks de novo purine biosynthesis and depends on purine salvage from the host. The purine salvage pathway is redundant and contains two routes to guanosine‐5′‐monophosphate (GMP) formation: conversion from xanthosine‐5′‐monophosphate (XMP) by GMP synthase (GMPS) or direct salvage of guanine by hypoxanthine‐guanine phosphoribosyltransferase (HGPRT). We show recombinant T. brucei GMPS efficiently catalyzes GMP formation. Genetic knockout of GMPS in bloodstream parasites led to depletion of guanine nucleotide pools and was lethal. Growth of gmps null cells was only rescued by supraphysiological guanine concentrations (100 μM) or by expression of an extrachromosomal copy of GMPS. Hypoxanthine was a competitive inhibitor of guanine rescue, consistent with a common uptake/metabolic conversion mechanism. In mice, gmps null parasites were unable to establish an infection demonstrating that GMPS is essential for virulence and that plasma guanine is insufficient to support parasite purine requirements. These data validate GMPS as a potential therapeutic target for treatment of human African trypanosomiasis. The ability to strategically inhibit key metabolic enzymes in the purine pathway unexpectedly bypasses its functional redundancy by exploiting both the nature of pathway flux and the limited nutrient environment of the parasite's extracellular niche.